162k views
0 votes
Evaluate the following expression
Find 2x - 3y - z if x = -2, y = 3, and z = -2

User Darrickc
by
5.4k points

2 Answers

4 votes

Answer:

-11

Explanation:

What we are solving for: 2x - 3y - z

x = -2

y = 3

z = -2

We can just plug in the variables.


(2*-2) - (3*3) - (-2)


-4-9+2

Therefore, the answer is -11.

Hope this helped!!

User Jonathan Sanchez
by
4.3k points
0 votes

Answer:

-11

Explanation:

2x - 3y - z

2(-2) - 3(3) - (-2)

-4 -9 +2

-13+2

-11

User TWest
by
5.0k points